Herding behaviour in a peripheral European stock market: the impact of the subprime and the European sovereign debt crises - dos Santos, L. G. G. (2018)
The characteristics of the Portuguese stock market suggest that it is susceptible to herding behaviour. We investigate the existence of this behaviour in Portugal during periods of market stress, with emphasis on the subprime and European sovereign debt crises. We analyse the overall stock market, key industries, and portfolios divided by market capitalisation. The study is performed using both linear and nonlinear models, and the impact of conditional variance is taken into account. This paper shows evidence of herding behaviour when the nonlinear model is used and during periods of crisis. Investors imitate more assets of similar size than assets of the same industry. Finally, the evidence of herding behaviour is reduced when GARCH effects are taken into account.